Immunomodulatory effects of potent bioactive compounds derived from plants - Budhbhatti, Nirali (International Journal of Psychosocial Rehabilitation, 2020)
Plants are able to produce diverse group of bioactive components. Components of several plants have been reported to possess immunomodulatory activity and can help improving immunity as well as potential source of drug in various diseases. Various alkaloids, flavonoids, terpenoids, polysaccharides, lactones, and glycoside products are responsible to cause alterations in the immunomodulatory properties, which can modulate immune system in a specific or nonspecific manner influence any constituent. The scientific community is devoting efforts towards traditional medicine and plant-based therapeutics, due to tremendous potential of the plants and their derived drugs. This review focuses on the immunomodulatory potential of common fruiting plants.